Vitamin D is a predictor of ST segment resolution and infarct size following thrombolysis in patients with acute ST elevation myocardial infarction - Ahmad Separham; Bahram Sohrabi; Leili Pourafkari; Nazli Sepasi; Samad Ghaffari; Naser Aslanabadi; Nader D Nader (KARE Publishing, 2017)
Objective: Vitamin D (VitD) insufficiency is linked to various chronic conditions, including cardiovascular disease. Aim of the present study was to examine role of serum VitD in resolution of ST segment elevation (STR) in response to thrombolytic therapy following acute ST elevation myocardial infarction (STEMI). Methods: VitD was measured prospectively in all consecutive patients who were admitted with STEMI and received thrombolysis during the calendar year of 2014. STR was defined as ≥50% decrease in initial magnitude of STR 90 minutes after treatment. Multivariate binary logistic regression analysis was performed to identify effect of confounding variables on STR. Results: Average age was 58+-14 years in 227 patients (41 female and 186 male). Total of 24.7% of patients had sufficient VitD (>30 ng/mL), whereas 46.2% had VitD insufficiency (10-30 ng/mL), and remaining 29.1% had VitD deficiency (<10 ng/mL). Significant STR occurred in 57.3% of the patients. In a nonlinear pattern, serum VitD concentration directly correlated with likelihood of STR (p=0.012). VitD deficient patients had larger enzymatic infarct size compared with those with sufficient VitD (p=0.026). In multivariate logistic regression analysis, while diabetes doubled (p=0.033) and involvement of anterior wall created 2.7-fold increase in probability of non-resolution (p=0.001), for every unit increase in serum VitD, likelihood of STR increased by 2.1% (p=0.023). Conclusion: VitD deficiency in patients with STEMI was associated with lower occurrence of STR and larger enzymatic infarct size in response to thrombolytic therapy.